Influence of Design Parameters of Anchor on Dyke Slope Stability - ZHENG Changhai; ZHAO Yuhao; YAN Chengming (Renmin Zhujiang)
Anchor is a commonly used supporting component in slope engineering,and its design parameters have a great influence on its anchoring effect.This paper studies the influence of length,spacing,inclination,anchoring area and anchoring length of anchors on the anti-slide safety factor of the slope,based on the numerical simulation of stability of dyke slope reinforced by anchors.The results show that:At a certain inclination,with a increase in anchor length,the safety factor increases first and then becomes steady,and there is an effective anchor length.The optimal anchor length decreases with anchor spacing increasing.Under certain anchor spacing,the safety factor increases at first and then decreases with anchor inclination increasing,and there is an optimal anchor inclination.The optimal anchor inclination decreases with anchor length increasing.Under different anchoring areas,with anchor length-to-spacing ratio increasing,the safety factor remains basically unchanged at first and then gradually increases,and with anchoring area increasing,the critical optimal anchor length-to-spacing ratio increases.With anchoring length increasing,the safety factor first increases and then remains basically unchanged,and there is an optimal anchoring length.